Literary dialect as social deixis. (November 2020) - Stockwell, Peter
The representation of non-standard and regional accent and dialect in literary fiction has been framed mainly sociolinguistically and treated as an index of authenticity, within an account of characterisation. The reader's attitude to such speakers in literary fiction is manipulated narratorially and authorially. Since readerly effects, impressions and evaluations are the key issues involved, it seems plausible that a cognitive poetic approach to the reading of dialect in literature would also be productive. In the current deictic theory, the dimension of social deixis captures a broad range of stylistic features including register and dialectal representations. Cognitive deictic theory draws on an explicitly spatial metaphor in which characters are positioned in conceptual space. However, insufficient attention has been paid to the effect of readerly positioning and dispositioning. This article revisits social deixis and its points of transition and textural variation from a theoretical perspective. It develops a new angle on the representation and significance of accented and dialectal forms in literary fiction, with some illustrative examples drawn from 19th and 20th century British novels.